Formation of picosecond laser-induced periodic surface structures on steel for knee arthroplasty prosthetics - Khuzhakulov, Zikrulloh; Kylychbekov, Salizhan; Allamyradov, Yaran; Majidov, Inomjon; Ben Yosef, Justice; Er, Alper Yusuf; Kitchens, Chazz; Banga, Simran; Badarudeen, Sameer; Er, Ali Oguz (Frontiers in Metals and Alloys, 2023)
The formation of laser-induced periodic surface structures (LIPSS) on mirror-polished 304-grade stainless steel sheet with dimensions 25mm x 25 mm x 0.8 mm surfaces upon irradiation with picosecond laser pulses in air and water environment at different laser energy wavelengths, number of pulses, and densities were investigated. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to characterize the LIPSS patterns. The tunable LIPSS periodicity was observed in both mediums at different wavelengths and fluence. Fluence was shown to be the main parameter on LIPSS formation while medium also plays an important role. Our result shows that LIPSS on stainless steel can be successfully generated in a single-step process and it can be easily modified with main laser parameters.